Safeguarding food safety: Nanomaterials-based fluorescent sensors for pesticide tracing - Marimuthu, Murugavelu; Xu, Kuncheng; Song, Wei; Chen, Quansheng; Wen, Hongli (Food chemistry, 2025)
Pesticide residue contamination has emerged as a critical concern due to its potential negative effects on both public health and the natural environment. Consequently, the detection of pesticide residue is of utmost importance. Nanomaterial-based fluorescence sensors, including metal nanoparticles (MNPs), metal nanoclusters (MNCs), carbon dots (CDs), and quantum dots (QDs), are particularly effective for detecting pesticide residues. Herein, we provide a comprehensive review of the recent advances (2018–2024) in fluorescence-based sensors utilizing MNPs, MNCs, CDs and QDs and their composites for the purpose of detecting various pesticides including organophosphates, carbamates, organochlorines, and pyrethroids in food. This review delves into the evolution of nanomaterials, their corresponding fluorescence-based sensing mechanisms, including Förster resonance energy transfer (FRET), photoinduced electron transfer (PET), inner filter effect (IFE), aggregation induced emission (AIE), and the detection principle, focusing on aspects of sensitivity and specificity. We also address the challenges and future perspectives of nanomaterials-based fluorescence sensors. [Display omitted] •The recent advance of nanomaterial-based fluorescence sensors to detect pesticides is reviewed.•The sensors design, development, working principle, and analytical performances are summarized.•Discussing the challenges and future perspectives of fluorescence sensors for food safety.